An effective learning culture: Using high performance work systems to strengthen the relationship between communities of practice and knowledge creation in Africa - Nansubuga, Florence; Munene, John C.; Kikooma, Julius; Nansamba, Joyce; Musanje, Khamis (Africa Journal of Management, 2019)
This paper sought to demonstrate how communities of practice can coalesce with high performance work systems to develop an Africanized learning culture that promotes interaction among employees and empowers them to create innovative knowledge for competitive performance. A total of 622 individual participants were selected from medium- and large-sized organizations (>200 employees) to complete data collection questionnaires. Structural equation modeling (path analysis coefficients) revealed that both components (hard and soft) of high performance work systems have significant mediating effects on the relationship between communities of practice and knowledge creation. However, adoption of the soft component of high performance work systems in knowledge creation seemed to be more relevant to African social learning practices and operational contexts.
Keywords: effective learning; high performance; knowledge creation; Africa